Barriers to generating PDX models of HPV‐related head and neck cancer. (31st May 2017) - Facompre, Nicole D.; Sahu, Varun; Montone, Kathleen T.; Harmeyer, Kayla M.; Nakagawa, Hiroshi; Rustgi, Anil K.; Weinstein, Gregory S.; Gimotty, Phyllis A.; Basu, Devraj
Abstract : Objectives/Hypothesis: Delineate factors impacting the creation and use of patient‐derived xenografts (PDXs) of human papilloma virus‐related (HPV+) head and neck squamous cell carcinomas (HNSCCs). Study Design: Laboratory‐based translational study. Methods: Fifty‐one surgically resected HNSCCs, including 31 HPV + cancers, were implanted into NOD/SCID/IL‐2Rγ ‐/‐ (NSG) mice using standardized methodology. Clinical and pathologic factors were tested for association with engraftment. The gross, histologic, and molecular features of established HPV + PDXs were analyzed in comparison to their tumors of origin. Results: Negative HPV status and perineural invasion (PNI) were independent, additive factors associated with increased PDX formation. Epstein‐Barr virus–positive (EBV+) human large B‐cell lymphomas grew from 32% of HPV + HNSCC cases that failed to engraft. Successfully established HPV + PDXs retained basaloid histology and often developed cystic growth patterns typical of HPV + nodal metastases. They also maintained elevated p16 INK4A levels and expression of E6/E7 viral oncogene transcripts. Conclusion: Reduced engraftment by HPV + tumors lacking PNI likely results in selection biases in HNSCC PDX models. Formation of EBV + lymphomas in NSG mice further reduces the generation of HPV + models and must be ruled out before long‐term use of PDXs. Nevertheless, the retention of distinctive pathologic traits and viral oncogene expression by HPV + PDXs provides a viable in vivo platform for basic and translational studies as well as a resource for generating advanced in vitro models. Level of Evidence: NA. Laryngoscope, 127:2777–2783, 2017